Caracterização de micro e nanofibras de PLA produzidas através da fiação por sopro em solução com a incorporação de óleo de candeia e a-bisabolol - Martins, Martina Fonseca (2015)
In the emerging field of nanostructured materials, there are the polymeric nanofibers, because to its large number of possible applications, such as in drug delivery systems because of their ability to bioabsorbilidade and controlling the rate of active substances encapsulated. The nanofibers may be produced by various techniques, including blow spinning solution (SBS), which can be used to produce micro and nanofibers at lower cost compared to other techniques. One of the most commonly used polymers for this purpose is poly (lactic acid) PLA, due to its biodegradability and biocompatibility. The aim of this study was to produce micro and nanofibers of PLA, using the SBS technique, with and without the addition of different contents of candeia (Eremanthus erythropappus) essential oil and its main fitoconstituint, the α-bisabolol. Due to the hydrophobicity of the PLA, as well known, they have also been produced webs containing DMSO, which acted as a surfactant since it is an organic compound with high hygroscopic capacity. Produced mats were characterized by SEM, TGA, DSC, XRD and FTIR. Results showed the immiscible nature of the produced polymer solutions. The addition of DMSO, of candeia oil and the α-bisabolol generated an increase in fiber diameters, as well as its distribution. The crystallographic analysis showed the semi-crystalline nature of the PLA, and a result contrary to that found in DSC for crystallinity, which was not discarded because it is different techniques. It can be concluded micro- and nanofibers of PLA with the addition of candeia oil and α-bisabolol were successfully produced by the SBS technique and that, in relation to the physicochemical properties of the mats produced, there was no differences encapsulate the candeia oil or α-bisabolol in nanofibers of PLA. The candeia oil potential applicant for use in polymeric nanostructured devices. This, according to the literature and after a few tests, such as the evaluation of antimicrobial activity, for example, could confirm their use in a drug delivery system in biomedical applications, as well as in various other cosmetic applications.